Hypertriglyceridemia Independent Propofol-Induced Pancreatitis - Muniraj, Thiruvengadam; Aslanian, Harry R (JOP. Journal of the Pancreas, 2012)
Context Propofol can cause acute pancreatitis related to hypertriglyceridemia, however, other mechanisms may also exist. Case report A 71-year-old male on propofol infusion in the intensive care setting, developed acute pancreatitis as confirmed biochemically and by imaging. He did not have any elevation of triglycerides and on propofol re-challenge, had recurrence of pancreatitis with the absence of triglyceride elevation. Conclusion We report a case of hypertriglyceridemia independent propofol induced pancreatitis possibly related to an idiosyncratic reaction and propose that this drug to be reassigned as a class Ia drug as an etiologic factor for acute pancreatitis. Image: Edematous acute pancreatitis.